2022
DOI: 10.1177/13607804211058744
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Healthcare Preferences Among EU Nationals in the UK: A Qualitative Assessment

Abstract: This article explores the motivational factors behind preferences for medical care in the country of residence or the country of origin among EU nationals living in the UK. Undertaking a thematic analysis on a large-N qualitative data set, the article aims to establish a data-driven typology of motivations inductively. This provides an intermediary analysis between qualitative depth and quantitative operationalisability, contributing to the existing literature on healthcare location preferences among transnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Although most CEE migrants within the 16 publications utilised healthcare in their CoO either exclusively or in addition to the NHS, three studies revealed that some CEE migrants used healthcare exclusively in the United Kingdom [ 49 , 50 , 51 ]. Reasons included convenience and cheaper cost.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most CEE migrants within the 16 publications utilised healthcare in their CoO either exclusively or in addition to the NHS, three studies revealed that some CEE migrants used healthcare exclusively in the United Kingdom [ 49 , 50 , 51 ]. Reasons included convenience and cheaper cost.…”
Section: Resultsmentioning
confidence: 99%
“…Financial considerations were a major factor, as certain migrants could not afford the costs associated with utilising healthcare in their CoO, which usually consisted of purchasing airfare and health services abroad. Moreh, McGhee, and Vlachantoni [ 49 ] described migrants who solely used NHS healthcare had made this decision as part of their perceived identity as United Kingdom residents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the flow of patients from the U.K. to Poland since the mid-2000s is mostly constituted of migrants seeking to access healthcare in their home country ( Horsfall, 2020 ). Returning to the country of origin to access medical services is common to other Europeans living in the U.K. ( Moreh, McGhee, and Vlachantoni, 2018 ) and has been found for Poles in several of EU countries ( Mathijsen, 2019 , Migge and Gilmartin, 2011 , Main, 2014 ). By moving from Poland to the U.K., Poles shift between state-funded health systems and lose access to public services in Poland, while becoming entitled to the use of the National Health Service (NHS) in the U.K.. Poles access most of the services in Poland within the private healthcare sector ( Troccoli et al., 2021 ), thus they seek healthcare “on their own initiative” outside the EU institutional routes ( Legido-Quigley et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%